Target Corporation, Inc. equity valuation - Monteiro, Catarina Vinhas (2023)
The main objective of this dissertation is to carry out the equity valuation of Target Corporation, a retail company based in the United States of America that belongs to the S&P index 500, in order to determine the price per share. Firstly, an industry analysis in which the company operates was carried out, thus, the North American market was characterized, the main competitors identified, as well as the opportunities and challenges of the sector.It was also analyzed the global economic context and its impact on the retail sector. On the other hand, the financial history of some company indicators was analyzed in order to deepen knowledge about it and choose the most suitable methods. The main method used was Discounted Cash Flow (DCF), having been determined an intrinsic value of $124.64. Comparing this value with the market value, $129.94 (16ℎ November 2023), a HOLD recommendation on the shares of Target Corporation share’s was issued. A relative assessment using multiples was performed, however it was discarded due to the difficulty in identifying a peer group that could be compare to Target Corporation.